Praktik Muamalah Tradisional dan Penyelesaian Sengketa dalam Masyarakat Banjar - Safitri, Maulidita; Pradana, Neco Erlin; Ramadhana, Yulia; Rukmawati, Desyana Putri; Putri, Riska Yunita; Rahmaniah, Amelia; Hanafiah, M. (Sharia Journal and Education Center Publishing, 2025)
The Banjar community is recognized as an ethnic group with a strong integration of Islamic teachings and local customs in its social and economic life. Traditional muamalah practices, particularly in buying and selling transactions, reflect the internalization of Islamic legal principles within long-standing local traditions. In addition, the Banjar people have a distinctive mechanism for dispute resolution known as adat badamai, which emphasizes deliberation, peace, and the restoration of social harmony. This study aims to examine traditional muamalah practices of the Banjar community and their dispute resolution mechanisms from the perspective of Islamic economic law and local wisdom. This research employs a qualitative approach using library research methods. Data were collected from relevant literature, including books, academic journals, and previous studies. The findings indicate that the tradition of explicitly pronouncing contractual statements (ijab qabul) in Banjar buying and selling transactions is consistent with the principles of Islamic muamalah and does not contradict Islamic law. Furthermore, dispute resolution through adat badamai reflects the values of justice, public interest (maslahah), and peace, which are central objectives of Islamic law. This study concludes that Banjar traditional muamalah practices and dispute resolution mechanisms remain highly relevant as models of local wisdom–based dispute settlement within contemporary Islamic legal and social contexts.